Strukturalistyczna bohemistyka Profesora Jacka Balucha (1940–2019) - Gierowski, Piotr (Przestrzenie Teorii, 2019)
Gierowski Piotr, Strukturalistyczna bohemistyka Profesora Jacka Balucha (1940–2019) [The Structural Bohemistics of Professor Jacek Baluch (1940–2019)]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 455–467. ISSN 1644-6763. DOI 10.14746/pt.2019.32.25. The paper describes the scientific profile of Jacek Baluch, Polish scholar and scientist in the field of Czech studies, professor of the Jagiellonian University, democratic opposition activist in the communist period in Poland, and Polish ambassador to Prague. The study emphasizes the structural aspects of Jacek Baluch’s scientific work and its meaning for the development of Polish literary knowledge in the second half of the 20th century.